2021
DOI: 10.2196/27965
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and Effectiveness of a Healthy-Coping Intervention via Chatbot for University Students During the COVID-19 Pandemic: Mixed Methods Proof-of-Concept Study

Abstract: Background University students are increasingly reporting common mental health problems, such as stress, anxiety, and depression, and they frequently face barriers to seeking psychological support because of stigma, cost, and availability of mental health services. This issue is even more critical in the challenging time of the COVID-19 pandemic. Digital mental health interventions, such as those delivered via chatbots on mobile devices, offer the potential to achieve scalability of healthy-coping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…Another interesting finding is that adaptive coping strategies, such as planning and positive reframing, work as protective factors against loneliness. This is a relevant finding considering that coping strategies may easily change following specific psychosocial interventions, such as psychoeducation (87,88) and problem-solving oriented interventions (89) or by improving the levels of resilience (25,81,90,91).…”
Section: Discussionmentioning
confidence: 97%
“…Another interesting finding is that adaptive coping strategies, such as planning and positive reframing, work as protective factors against loneliness. This is a relevant finding considering that coping strategies may easily change following specific psychosocial interventions, such as psychoeducation (87,88) and problem-solving oriented interventions (89) or by improving the levels of resilience (25,81,90,91).…”
Section: Discussionmentioning
confidence: 97%
“…Yet another important factor to consider is whether a 2-week intervention is long enough to impact positive affect in the context of a significant stressful event, such as a global pandemic. To date, a few short-term interventions have been utilized to promote mental health during the COVID-19 pandemic, with success in increasing positive affect (Brouzos et al, 2021 ), while reducing anxiety, depression, perceived stress, and loneliness (Brouzos et al, 2021 ; Riva et al, 2021 ; Wei et al, 2020 ; Gabrielli et al, 2021 ). While the mode of delivery spanned from self-help and virtual reality (Wei et al, 2020 ; Riva et al, 2021 ) to group or individual formats (Gabrielli et al, 2021 ; Brouzos et al, 2021 ), one consistent factor was that each study incorporated aspects of mindfulness and relaxation exercises in addition to activities consistent with positive psychology and cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A case report on young adults with a psychotic illness found digital phenotyping via tracking on a smartphone app is a feasible way to monitor and detect patient status [82]. A proof-of-concept study with university students found early evidence that there is benefit in deploying a digital healthy-coping intervention via a chatbot for their higher levels of psychological distress [83]. There was preliminary evidence of efficacy for digital psychological interventions via games and virtual reality (VR) in children and young people [84].…”
Section: Digital Mental Health For Young Peoplementioning
confidence: 99%